2004
DOI: 10.1007/s00259-004-1581-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical feasibility of two-step streptavidin/111In-biotin scintigraphy in patients with suspected vertebral osteomyelitis

Abstract: Streptavidin/111In-biotin scintigraphy is highly sensitive and specific for detecting vertebral osteomyelitis in the first 2 weeks after the onset of clinical symptoms, and is potentially very useful for guiding clinical decisions on instituting appropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Approximately 50% of cases present as areas of nonspecific decreased activity (4). (19,20). 18 F-FDG imaging consistently outperforms bone, 67 Ga, and antigranulocyte antibody imaging and compares favorably with MRI (21-30).…”
Section: Spondylodiskitismentioning
confidence: 91%
“…Approximately 50% of cases present as areas of nonspecific decreased activity (4). (19,20). 18 F-FDG imaging consistently outperforms bone, 67 Ga, and antigranulocyte antibody imaging and compares favorably with MRI (21-30).…”
Section: Spondylodiskitismentioning
confidence: 91%
“…Radiolabeled biotin derivatives can be used as targeted diagnostic and therapeutic radiopharmaceuticals in nuclear medicine. They have been evaluated in the clinical practice for the scintigraphic diagnosis of skeletal infections with favorable results . In addition, radiolabeled biotin derivatives have been evaluated in cancer pretargeted radioimmunoscintigraphy (RIS) and radioimmunotherapy (RIT), an approach with considerable advantages over the conventional RIS/RIT.…”
Section: Introductionmentioning
confidence: 99%
“…Its high affinity for biotin has been used for a variety of biological and analytical research by coupling with various reporter probes, such as fluorescence dyes, radioactive elements or enzymes. In addition, biotin-streptavidin system is also applied to human clinical medicine for cancer diagnosis, radioactive imaging and pre-targeted immunotherapy [3,4,5,6]. Previous studies reported that administration of streptavidin after heart transplant prolonged survival and streptavidin suppressed T cell proliferation in mixed splenocyte culture [7,8].…”
Section: Introductionmentioning
confidence: 99%